Interrelationship between screen time, playfulness, parental monitoring and emotional intelligence among Chinese preschool children in Kuala Lumpur, Malaysia - Tun, Ju Ern (2021)
Emotional intelligence develops during the crucial early stage of age among preschool children and many negative impacts may arise and affect their lives due to the deficits in emotional intelligence. The purpose of the present study is to determine the relationship between screen time, playfulness, parental monitoring and emotional intelligence among Chinese preschool children in Kuala Lumpur. Additionally, this study wishes to find out the unique predictor of emotional intelligence and whether child’s sex and parental monitoring would play moderating roles in these relationships. There were 217 mothers of Chinese preschool children aged between four to six years old study at selected private preschools in Kuala Lumpur were recruited as respondents in this study by using Stratified Proportionate Random Sampling technique. Selfadministered questionnaire was distributed to mothers. Children’s screen time was assessed by using Screen Time Questionnaire (STQ), whereas the information of playfulness was collected by using Child Behavior Inventory of Playfulness (CBI). Adult Involvement in Media Scale (AIM) was employed to measure parental monitoring and lastly Parent Rating Scales of Emotional Intelligence was utilized to assess children’s emotional intelligence. All instruments used in the current study showed good reliability in the local context with overall reliability score of above .70. As the results, there was no significant relationship between screen time and emotional intelligence. However, playfulness (r = .42, p < .01) and parental monitoring (r = .35, p < .01) were significantly positive correlated with emotional intelligence. Besides, playfulness (β= .29, p < 0.00) and parental monitoring (β= .27, p < 0.00) were found as predictors of emotional intelligence. Nevertheless, child’s sex and parental monitoring could not consider as moderators in this study. In sum, the study provides valuable information to parents on how screen time, playfulness and parental monitoring influence emotional intelligence among preschool children.